Diagnóstico da implementação dos Objetivos de Desenvolvimento Sustentável (ODS) a partir das leis orçamentárias municipais brasileiras - Simões, Maria do Socorro de Lima (2024)
This research aimed to analyze how the Sustainable Development Goals (SDGs) were implemented based on Brazilian municipal budget laws. To find it, qualitative, quantitative and descriptive research was carried out, covering: analysis of municipal indices; questionnaire application; documentary analysis of municipal guidelines in this area. An additional 5,000 municipalities were contacted via Google Forms, with responses from 81 of them: 46 cities stated that they had implemented the SDGs based on budgetary laws. A regional analysis was carried out, considering two categories: budgetary and financial compliance, based on normative instruments, such as the LRF; performance, related to means of surveying, analyzing and implementing actions. The Chi-square test and Simple Correspondence Analysis (ANACOR) were also carried out, involving associations between actions, criteria and contributions from the Multi-Year Plan (PPA), the Budget Guidelines Law (LDO) and the Annual Budget Law (LOA). This test found associations between actions, prices and contributions of these laws to meeting the SDGs. The Southeast and South regions tended, in general, towards budgetary performance, highlighting associations related to: UN 2030 Agenda; previous budget executions; projects and processes. In other regions, mainly in the Northeast, the biggest emphasis was on budget compliance, with an emphasis on: accountability; fiscal targets; compatibility of the Fiscal Responsibility Law (LRF) and population demands; participatory budgeting. The concentration of the best results in the Brazilian Cities Development Index (IDSC BR) was also noted in the population range “100,001 – 500,000”, with the following highlights: Jundiaí (SP); Maringá (PR); Sobral (CE); Palmas (TO). The mentioned associations were reflected in the IDSC BR and municipal Human Development Index (HDI). It is hoped that this research can contribute to the promotion of regional actions, as well as to in-depth studies on the contributions of budget laws and the growth of municipal GDP